Acquiring embodied and institutionalized cultural capital : career development and success among Slovenian football players - Križaj, Jožef (Array, 2021)
The main objective of this study was to determine whether sociocultural factors influence the career development of Slovenian national team football players. In this interview-based research, we consider Bourdieu"s theory of embodied and institutionalized cultural capital to find possible influencing sociocultural factors on the career development. Semi-structured interviews were conducted with eight Slovenian elite football players. The content of the interviews was organized based on the chronological events in each player"s life using seven open-ended questions. We analysed careers from the very beginning (initiation), across the development and mastery period to the career peak of the Slovenian football players in terms of the migration abroad. The results of this study support previous studies on the career development of football players. The work shows the important role of primary and secondary socialization processes, which exert a significant influence on career development among Slovenian football players.